Changes in Nasalance and Velopharyngeal Function Following Conventional Le Fort I and Distraction Osteogenesis Using Perceptual and Instrumental Assessment. Issue 2 (June 2022) - Schleif, Eshan Pua; Dillon, Katherine; Brady, Colin M.; Williams, Joseph K.; Riski, John E.; Perry, Jamie L.
Objective: The objective of this study was to quantify the changes in nasalance and velopharyngeal function in individuals with repaired cleft palate who underwent conventional Le Fort I (LFI) and Distraction Osteogenesis (DO). This study will also examine changes relative to secondary factors of age, cleft type, and previous speech surgery. Methods: This retrospective study included 19 patients who underwent LFI and 24 patients who underwent DO at a tertiary level pediatric hospital from 2011 to 2019. All patients had repaired cleft palate and were between 7 and 18 years of age. Pre- and post-operative speech assessment was completed before and after surgery. Results: There was a significant increase in nasalance scores for the oral sentences of 12.9% for the LFI group ( P  = .006) and 17.9% for the DO group ( P  < .001). A significant difference in nasalance scores between patients with and without previous speech surgery in the LFI group. Conclusions: Findings may aid surgeons and speech pathologists in informing patients about the potential increase in nasalance following LFI or DO. Findings may indicate that timing of speech surgery is more favorable before LFI, but not influential for individuals undergoing DO.